Dissections : - Frederickson, Greg N. (Cambridge University Press, 1997)
Can you cut an octagon into five pieces and rearrange them into a square? How about turning a star into a pentagon? These are just two of the infinite challenges of geometric dissections, the mathematical art of cutting figures into pieces that can be rearranged to form other figures, using as few pieces as possible. Through the ages, geometric dissections have fascinated puzzle fans and great mathematicians alike. Here are dissections known to Plato and exciting new discoveries alike. Greg Frederickson explains solution methods carefully, assuming only a basic knowledge of high school geometry. This beautifully illustrated book provides hours of enjoyment for every mathematical puzzle enthusiast.